Multitarget Molecular Docking Using Curcuma longa Phytocompounds for Polycystic Ovary Syndrome Treatment - Basamma D.B. (International Journal of Molecular Biotechnological Research, 2024)
Objective: The primary goal of this research is to understand and describe specific aspects of molecular interaction, it includes studying various aspects such as binding affinity, binding mode, and stability of the ligand-protein complex. Molecular docking is a computational technique used to predict the preferred orientation of one molecule to a second when bound together to form a stable complex. In this study, molecular docking will be employed to stimulate and analyze the interaction between the ligand and the target protein. Identifying the phytocompounds for the treatment of Polycystic ovary syndrome involves exploring the plant-derived compounds with potential therapeutic effects on the symptoms and underlying mechanisms of the condition. Methods: In this study, an in silico study to develop the best phytocompounds to treat polycystic ovary syndrome (PCOS). IMPPAT database was used to retrieve the phytocompounds from Curcuma longa. The molecules selected underwent drug-likeness screening on SwissADME, and final screening was conducted using PyRx software, revealing the binding affinity between the ligands and the 1h59 target protein. The examination of 3D interactions was carried out using BIOVIA. Results: The potential lead molecules are Cinnamyl cinnamate, ar-Turmerone, and alpha-curcumene from Curcuma longa were identified to resist the insulin which helps to treat polycystic ovarian syndrome. Conclusion: All three compounds, namely cinnamyl cinnamate, ar-Turmerone, and alpha-curcumene, comply with Lipinski’s parameters, indicating their suitability for treating PCOS by regulating insulin levels. These lead molecules show prominent results in polycystic ovarian syndrome.
Keywords: ADME analysis; Curcuma longa; Lipinski rule of 5; insulin-like growth factor1; molecular docking; phytocompounds